2019
DOI: 10.1117/1.jbo.24.5.051408
|View full text |Cite
|
Sign up to set email alerts
|

fNIRS improves seizure detection in multimodal EEG-fNIRS recordings

Abstract: In the context of epilepsy monitoring, electroencephalography (EEG) remains the modality of choice. Functional near-infrared spectroscopy (fNIRS) is a relatively innovative modality that cannot only characterize hemodynamic profiles of seizures but also allow for long-term recordings. We employ deep learning methods to investigate the benefits of integrating fNIRS measures for seizure detection. We designed a deep recurrent neural network with long short-term memory units and subsequently validated it using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…In addition to this, there are several fNIRS based ML studies that focuses on classification of several psychiatric disorders also uses ΔHb (Cheng et al, 2019; Crippa et al, 2017; Hernandez-Meza et al, 2018; Hernandez-Meza et al, 2017; J. Li et al, 2016; Rosas-Romero et al, 2019; Sirpal et al, 2019; Sutoko et al, 2019) and for some cases ΔHb based features might also show higher accuracy results compared to ΔHbO based ones (Crippa et al, 2017). After estimating the CC based FC matrix, it was normalized by performing Fisher’s z-transformation due to reduce skewness.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to this, there are several fNIRS based ML studies that focuses on classification of several psychiatric disorders also uses ΔHb (Cheng et al, 2019; Crippa et al, 2017; Hernandez-Meza et al, 2018; Hernandez-Meza et al, 2017; J. Li et al, 2016; Rosas-Romero et al, 2019; Sirpal et al, 2019; Sutoko et al, 2019) and for some cases ΔHb based features might also show higher accuracy results compared to ΔHbO based ones (Crippa et al, 2017). After estimating the CC based FC matrix, it was normalized by performing Fisher’s z-transformation due to reduce skewness.…”
Section: Methodsmentioning
confidence: 99%
“…Chiarelli et al ( 2018 ) found a significant increase in classification accuracy for multimodel EEG-fNIRS recording than standalone EEG and fNIRS signals and other classification algorithms. Sirpal et al ( 2019 ) proposed a deep recurrent neural network for seizure detection in multimodel EEG-fNIRS recording and found that this promising framework can be used in future EEG-fNIRS models to make detection and prediction.…”
Section: Hybrid Eeg-fnirs-based Bcimentioning
confidence: 99%
“…103 A model based on long short-term memory in the recurrent neural networks demonstrated an e±cient performance in seizure detection in a hybrid EEG-fNIRS study. 104…”
Section: Resting Statementioning
confidence: 99%
“…Few studies could examine most of the brain regions. 85,91,104,108,229 Neuronal activations occurring in response to a single task are not linked to a single brain location. 351 Therefore, the outcomes of the studies that focus on a speci¯c narrow location in the brain might not be su±cient for understanding the brain functions.…”
Section: Channel Resolution and Limitationmentioning
confidence: 99%